Análise das práticas decisórias de novatos e experts no processo de inovação - Frederico Cesar de Vasconcelos Gomes (2013)
Innovation is able to change the rules of competition in a given sector, threatening the position of established firms and even create new markets. Despite the interest of academia, one of the main focuses of researches is based on the study of innovation in the perspective of the organization. Therefore, we sought to investigate the decision taken by individuals within the innovation process. It was found that these individuals possess different skill levels that can go from beginners to experts. The focus of this study was to understand how these individuals, beginners and experts, utilize models of innovation management to make their decision. We adopted this understanding to the triad: academia, incubators and market analysis for the skills of the practitioner of innovation and mapping the characteristics and skills of an expert and a novice in this process. It has thus become possible, through the reports obtained, analyze the similarities and distinctions between the practices adopted by individuals and organizations studied and the models established by the academy. To achieve this goal, Strategy Practice was methodologically employed. Through this methodology established itself the object of analysis: individuals with different levels of experience related to the innovation process. We conducted a series of interviews with experts and beginners who somehow were linked to the innovation process. From the analysis of these reports was possible to obtain a description of the possible trajectories of an individual within the process of innovation and its competence according to the degree of innovation. These same reports emerged that there are different types of experts about the degree of innovation, and we observed a specific set of skills. This distinction can be explained in the analysis of how each individual in a degree of innovation, adopts and applies the models of innovation management in its decision making process. It is hoped that this study assists in understanding how models of innovation management are adopted and used by individuals in their decision making processes and the types of existing experts in this process